Ferdinand Magellan opening the door to world exploration - Asimov, Isaac (Gareth Stevens Children's Books Milwaukee, 1991)
Presents the story of the Portuguese explorer who became the first European to cross the Pacific Ocean and whose expedition completed its voyage around the world after his death en route.
Includes bibliographical references and index.
8 - 10 years
Keywords: Magellan, Ferdinand -- 1521 -- Juvenile Literature; Explorers -- Portugal -- Biography -- Juvenile Literature; Voyages around the world -- Juvenile Literature; Explorers; Voyages around the world